고등학교 화학 I 과정 “물” 단원에서 학업성취도 평가문항의 내용타당도 분석 - 백성혜, 이은준, 김정수, 송영욱, 김용진, 정정인, 한재영 (교과교육학연구, 2008)
학교 교육에서 평가는 교육목표 달성 확인 및 교수 계획 수립에 중요한 역할을 한다. 따라서 학 생들의 학업성취도 평가는 높은 내용타당도를 가지고 있어야 한다. 즉, 학업성취도 문항은 수업목 표에 비추어 적절하고 학습한 내용을 포괄할 수 있어야 한다. 학교 현장에서 평가 문항의 타당도는 매우 중요한 반면, 실제 학교에서 사용되는 고등학교 화학 과목의 평가 문항들이 어느 정도 내용타 당도를 가지고 있는지 조사되는 경우가 거의 없다. 따라서 이 연구에서는 학교현장에서 실시되는 화학 학업성취도 평가문항이 행동차원과 내용차원에서 어느 정도의 내용 타당도를 가지는지 분석 하고자 하였다. 이를 위한 연구의 대상은 제7차 교육과정에 의하여 개발된 동일한 화학Ⅰ 교과서 를 교재로 사용하고 있는 5개 학교의 ‘물’ 단원에 대한 1학기 중간고사 평가문항이었다. 내용타당도 분석을 위한 과정은 첫째, 교과서와 교사용지도서에서 34개의 수업목표를 내용차원과 행동차원으 로 이원 분류하였다. 둘째, 5개 고등학교의 평가문항에서 121개의 평가문항을 행동차원과 내용차 원으로 이원 분류하였다. 셋째, 행동차원과 내용차원별로 각각 수업목표와 평가목표의 비율차 검 증을 하였다. 연구 결과, 5개 학교에서 사용된 학업성취도 문항은 행동차원에서의 내용타당도는 낮았지만 내용차원에서의 내용타당도는 높은 것으로 나타났다. 이는 고등학교에서 실시하는 학업 성취도 평가에 있어서 행동차원의 내용타당도를 높이는 노력이 좀 더 필요하다는 것을 시사한다. 특히 행동차원 중 분석력, 종합력, 평가력 등 고등정신기능을 기르는 평가 문항의 개발에 노력을 기울여야 한다. 이 연구를 통해, 평가 문항 제작에 대한 교사들의 전문성을 높이기 위해 다양한 연수나 교육 프로그램이 개발될 필요가 있음을 알 수 있다 In school education, the evaluation plays an important role for the accomplishment of educational goal and for the planing of education. Thus, the achievement evaluation item should have high validity. The achievement evaluation items should appropriate for the educational goal and include all the learning contents. Although the validity of achievement evaluation items is very important, little research was performed on how much the evaluation items of high school chemistry course really have the content validity. Therefore, in this study we analyzed the validity of the chemistry achievement evaluation items used in schools in the dimension of behavior and content. For this, 5 different high schools were selected that used the same publisher's chemistry I textbook, and the middle semester achievement evaluation items were gathered. First, 34 instructional objectives were classified into the behavior domain and the content domain from the 'water' chapter in the textbook and the teacher's guide. Second, 121 evaluation items were classified into the behavior domain and the content domain. Third, the analysis of the ratio difference method were performed between the instructional objectives and the evaluation objectives. From the results, it was found that content validities of the behavior domain were low, but those of the content domain were high. These results implies that more effort should be paid to raise content validities of the behavior domain in achievement evaluation of high schools. Especially, the test items should be developed on the high level thinking skill such as analysis, synthesis, and evaluation. This study tells it is necessary to develop in-service teacher education program to raise the professionality of teachers on the evaluation items. KCI Citation Count: 4